An experimental model of chemically-induced ulceration of the buccal mucosa of Mus musculus - Idrus, Erik; Hartanti, Pratiwi Dwi; Suniarti, Dewi Fatma; Prasetyo, Sri Redjeki; Wimardhani, Yuniardini Septorini; Subarnbhesaj, Ajiravudh (Makara Journal of Health Research, 2019)
Background: Ulceration caused by chemical agents used in dental practice for in-office or home-used is a common event, resulting in discomfort and pain. Treatments for such conditions are still being developed, requiring extensive experiments both in vitro and in vivo studies. At present, a standardized experimental mouse model for mucosal ulceration caused by a chemical inducer to study the pathogenesis of ulceration and to develop medications for treatment of ulceration is still not available. The aim of this study was to create a chemically induced model of ulceration of the buccal mucosa of mice. Methods: An in vivo study model of ulceration using a total of 9 mice (Swiss Webster) was performed. All mice received 70% acetic acid application on the left buccal mucosa, while the right buccal mucosa received only saline. Clinical and histological observations of ulcer formation and healing were performed, including the presence of redness and swelling, ulcer diameter, bodyweight as well as epithelial disintegration, dilation of blood vessels, and infiltration of inflammatory cells. Results: Buccal mucosa application of 70% acetic acid generated ulcers on day 2, reached its peak on day 3 and recovered by day 14. The histological features of inflammation were also seen in the ulcer model, and the degree of inflammation was consistent with the day of ulcers. Conclusion: Chemical trauma by the administration of 70% acetic acid effectively induce ulceration on buccal mucosa in mice, and this method can be considered as a novel, reproducible, and clinically relevant model to study pathogenesis and therapeutic approach for treating oral mucosal ulceration.